B vitamins supplementation induced shifts in phytoplankton dynamics and copepod populations in a subtropical coastal area - Wang, Lin; Zhao, Hancheng; Sanganyado, Edmond; Liang, Bo; Chen, Xiaohan; Ma, Qun; Lin, Jianqing; Liu, Wenhua (Frontiers in Marine Science, 2023)
Introduction B vitamins play a crucial role in shaping phytoplankton and zooplankton communities in marine ecosystems, yet their impact on community dynamics remains poorly understood. Methods We carried out in situ incubation experiments of B vitamins supplementation to explore the response pattern of phytoplankton and zooplankton community compositions. Results The results showed that vitamins B1, B2, B6 and B12 promoted the growth of phytoplankton, and the total Chl α in 87.5% of the supplemented B vitamin treatments showed a significant positive response (p < 0.05). Supplementation with these B vitamins significantly altered the community composition of phytoplankton, and 75% of the B vitamin-supplemented treatments showed an increase in the relative abundance of Minutocellus, Thalassiosirales, Odontella, Prymnesiales and Ditylum, considered mainly to be the result of B vitamin auxotrophy. In contrast, a significant decrease in Copepoda, including Calanoida and Cyclopoida, was observed in 87.5% of treatments. The observed shifts in community composition were attributed to the auxotrophy of certain diatoms and Prymnesiales for B vitamins. These shifts subsequently led to negative correlations (Spearman Rho < -0.8) between the abundance of these phytoplankton species and Copepoda populations. Discussion These findings advance our understanding of the complex interactions between micronutrient availability and plankton community dynamics.